Establishing reduced thermal mathematical model (RTMM) for a space equipment: an integrative review - Akbulut, Mustafa; Ertas, Ahmet H. (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this study is to, first, provide an overview of the previously conducted works related to thermal analysis of space equipment, including battery packages, especially lithium (Li)-ion ones. Second, the need for a reduced thermal mathematical model (RTMM) and a procedure devising it is defined. Finally, an experimental steady-state temperature distribution test is conducted to finalize the RTMM study. Design/methodology/approach This study was carried out as part of a development project for thermal analysis of Li-ion battery packages used in a space equipment. The study presents certain stages of the design of the battery pack in parallel with battery technology development. Following a literature review, a numerical thermal analysis is conducted; then interface thermal conductance values are found out by means of the first law of thermodynamics; and the study is completed with the help of an experimental test. Findings The study provides key aspects for a successful battery-package thermal design for a space equipment. Additionally, the study summarizes the experimental results used in the RTMM process and the computed thermal conductance values between node couples. Practical implications Thermal analysis is important and vital in space equipment considering their harsh working conditions and environments. Hence, the study provides a RTMM for the thermal analysis of Li-ion battery packages, instead of a full finite element model, to save computational time and CPU usage. The findings are supported by experimental results. Hence, presented details can be used as guidelines for enterprises having a goal of battery package technology achievement, including design and manufacturing. Originality/value After providing a literature review of studies conducted on satellite subsystems including Li-ion batteries, this study presents a clear, complete and verified process of a RTMM for a Li-ion battery package in aero/space structures design. It presents details of building up a model and calculation methodology through an iterative procedure in which an optimization algorithm known as particle swarm optimization (PSO) was benefitted. In the RTMM, additionally, experimental temperature distributions obtained through thermal vacuum test were presented. It has been shown that the model can be used reliably in designing space equipments.
Keywords: Particle swarm optimization (PSO); Thermal analysis; Lithium-ion battery; Reduced thermal mathematical model (RTMM)